THE FEATURES OF FUNCTIONING OF EARLY MALADAPTIVE SCHEMES (SCHEMA-MODES) CHARACTERISTIC FOR SECONDARY SCHOOL PUPILS WITH DIFFERENT ACADEMIC ABILITIES AND ACHIEVEMENTS - Shcherbakova, Olena (PSYCHOLOGICAL JOURNAL, 2019)
The research purpose was to study functioning of early maladaptive schemes (schema-modes) of secondary school pupils with different academic abilities and achievements. Methods. SMI-T - Schema Modes Inventory for adolescents, which is the version of the Schema Modes Inventory proposed by Young et al. and adapted by A.Bolshakov, was used to diagnose the early maladaptive schemes. The SMI-T questionnaire allows us to estimate ten schema-modes with the following scales: demanding / punishing parents, vulnerable child, angry / enraged child, bully and attack, impulsive / undisciplined child, compliant surrender, healthy adult, detached, self-aggrandizer, and happy child. The obtained data were processed statistically with one-way ANOVA and Student’s t-test. Results. Five typological profiles of academically successful pupils and three profiles of academically unsuccessful pupils can be distinguished depending on their academic abilities. The performed comparison of schema-modes characteristic for academically successful and unsuccessful pupils revealed some statistically significant differences. Academically successful pupils are more inclined, in comparison with unsuccessful ones, to such dysfunctional modes as a vulnerable child and a self-aggrandizer. Academically unsuccessful schoolchildren are more prone to such dysfunctional modes of an angry / enraged child, bully and attack, an impulsive / undisciplined child and a detached person. The performed comparison of schema-modes characteristic for pupils of eight typological profiles, based on different academic abilities and achievements, show the existing statistically significant differences for all evaluated functional and dysfunctional schema-modes. Academically successful pupils are more likely to be self-critical, demanding, and vulnerable to adverse influences of difficult situations and self-aggrandizement (modes: demanding / punishing parents, vulnerable child, compliant surrender, self-aggrandizes). Academically unsuccessful pupils are more aggressive, impulsive, and prone to compulsive distractions (modes: angry / enraged child, impulsive / undisciplined child, bully and attack, detached). Both, successful and unsuccessful, pupils with an intrinsic motivation to learn showed a tendency to the mode of a healthy adult. Conclusions. High academic achievements are not sufficient for life success and full-fledged functioning in all life spheres. Academically successful pupils, according to their examined typical cognitive, emotional and behavioural patterns of responses to stressful situations, do not have better psychological well-being than their peers. On the contrary, according to some schema-modes used by them, they exhibit less adaptive features. The development of psychological support programs for teaching of academically gifted secondary school pupils should include not only the development of their academic abilities, but also preventive and corrective actions regarding typical modes formed under parental influence.